2017
DOI: 10.1155/2017/6512572
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the TCM Qi‐Supplementing Therapy in Patients with Myasthenia Gravis: A Systematic Review and Meta‐Analysis

Abstract: Background The Traditional Chinese Medicine (TCM) Qi-supplementing therapy has been used widely for treating myasthenia gravis (MG) in China. The purpose of this meta-analysis was to evaluate the efficacy and safety of Qi-supplementing therapy as an adjunctive therapy in MG patients. Methods Seven electronic databases were searched through June 2016. Randomized controlled trials (RCTs) evaluating the add-on effect of Qi-supplementing therapy in MG patients were included. The outcome measures were the total eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Terefore, invigorating Qi is the basic principle of treatment for MG with Qi defciency syndrome. Clinically, HD has been widely used for the treatment of myasthenia gravis [4]. Studies have found that the main active components in HQ are saponins, favonoids, and astragalus polysaccharides, which are rich in immune active substances.…”
Section: Introductionmentioning
confidence: 99%
“…Terefore, invigorating Qi is the basic principle of treatment for MG with Qi defciency syndrome. Clinically, HD has been widely used for the treatment of myasthenia gravis [4]. Studies have found that the main active components in HQ are saponins, favonoids, and astragalus polysaccharides, which are rich in immune active substances.…”
Section: Introductionmentioning
confidence: 99%
“…MG is usually treated with conventional western medicine such as acetylcholinesterase inhibitors, glucocorticoid, and other non-steroidal immunosuppressants with dissatisfactory clinical effects in some patients, the risk of unconscionable dosage, and unwanted adverse effects where traditional Chinese medicine (TCM) can take a complementary and alternative effect. A study found that using TCM combined with western medicine might improve the total effect and reduce the risk of MG relapse [ 9 ]. According to the TCM characteristic theory of “spleen governing muscle,” MG is generally diagnosed as “spleen qi deficiency syndrome” and thereby, strengthening the spleen and replenishing qi is a common therapeutic strategy of MG in TCM, which has played a positive role in clinical practice of MG [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disorder of gut microbiota promotes immune in ammation response, which aggravates the severity of MG. (7,8) MG is usually treated with conventional western medicine such as acetylcholinesterase inhibitors, glucocorticoid and other non-steroidal immunosuppressants with dissatisfactory clinical effects in some patients, the risk of unconscionable dosage and unwanted adverse effect where Traditional Chinese medicine (TCM) can take a complementary and alternative effect. A study found that using TCM combined with western medicine might improve the total effect and reduce the risk of MG relapse (9) . According to the TCM characteristic theory of "spleen governing muscle", MG is generally diagnosed as "spleen qi de ciency syndrome" and thereby, strengthening spleen and replenishing qi is a common therapeutic strategy of MG in TCM, which has played a positive role in clinical practice of MG. (10,11) Buzhong Yiqi Decoction (BYD), a classical qi-supplementing formula in TCM, is the most frequently used prescription to treat MG. A study showed that BYD modulated the balance of Treg and Th17 cells in patients with MG, downregulated the serum AChR antibody level (12).…”
Section: Introductionmentioning
confidence: 99%